Life Satisfaction İn Relation To Self-Esteem, Self-Efficacy And Self-Compassion - Yashpal Singh; Davinder Singh Johal (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Life satisfaction in general, is considered as our evaluation of feeling, emotions, and sentiments about our own life and how pleased we are with it. Life satisfaction is a very critical parameter, therefore researchers are keen to investigate the various parameters which are going to affect it directly or indirectly. The present study was focused on to analyze the role of Self-esteem, Self-efficacy and Self-compassion which show direct or indirect association with the individuals Life satisfaction. The study use correlational research design. A sample of 102 individuals has been selected for this study from Delhi region of India.The findings obtained indicates a significant positive association between Self-esteem and Life satisfaction (r= 0.478) and regression analysis reveal that Self-esteem is considered as a vital predictor of Life satisfaction. The obtained values of correlation has also indicate a significant positive association between Self-efficacy and Life satisfaction (r= 0.337) and a significant positive association between Self-compassion and Life satisfaction (r= 0.379).The results clearly represents that Self-esteem, Self-efficacy and Self-compassion play crucial role for the development of Life Satisfaction among individuals.